Guided Multimodal Expressive Writing for Religious Character Development in Elementary Students - Lilis Sumaryanti; Happy Susanto; Siti Munawaroh; Nuraini; Muhammad Iqwanul Mustachim (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The development of religious character among elementary school students continues to face implementation challenges, as school literacy programs tend to emphasise cognitive aspects while insufficiently integrating reflective processes. This study aimed to examine the effectiveness of guided multimodal expressive writing in strengthening students’ religious character and to explain the underlying mechanisms of value internalisation. This study employed a mixed methods approach using a sequential explanatory design. The quantitative component used a pre-experimental one-group pretest–posttest design, involving 30 first-grade students from a Muhammadiyah elementary school selected through purposive sampling. The instruments included a religious character observation checklist, a multimodal work analysis rubric, and anecdotal records. Quantitative data were analysed using the Wilcoxon signed-rank test, while qualitative data were analysed through thematic analysis. The results showed significant improvements across all dimensions of religious character (p < 0.001), with large effect sizes (r = 0.75–0.87), particularly in religious awareness and social care. Qualitative findings indicated that these improvements were associated with the development of reflective processing, which enabled students to construct meaning from their experiences. This study contributes a structured model of guided multimodal expressive writing that integrates multimodal expression and reflective scaffolding to support value internalisation among early-grade students. These findings suggest that expressive writing can function as a pedagogical strategy within literacy programs to support the development of students’ religious character.